Adiponectin Limits IFN-γ and IL-17 Producing CD4 T Cells in Obesity by Restraining Cell Intrinsic Glycolysis - Surendar, Jayagopi; Frohberger, Stefan J.; Karunakaran, Indulekha; Schmitt, Vanessa; Stamminger, Wiebke; Neumann, Anna-Lena; Wilhelm, Christoph; Hoerauf, Achim; Hübner, Marc P. (Frontiers in Immunology, 2019)
Compared to the innate immune system, the contribution of the adaptive immune response during obesity and insulin resistance is still not completely understood. Here we demonstrate that high fat diet (HFD) increases the frequencies of activated CD4+ and CD8+ T cells and frequencies of T cells positive for IFN-γ and IL-17 in the adipose tissue. The adipocyte-derived soluble factor adiponectin reduces IFN-γ and IL-17 positive CD4+ T cells from HFD mice and dampens the differentiation of naïve T cells into Th1 cells and Th17 cells. Adiponectin reduces Th17 cell differentiation and restrains glycolysis in an AMPK dependent fashion. Treatment with adult worm extracts of the rodent filarial nematode Litomosoides sigmodontis (LsAg) reduces adipose tissue Th1 and Th17 cell frequencies during HFD and increases adiponectin levels. Stimulation of T cells in the presence of adipocyte-conditioned media (ACM) from LsAg-treated mice reduces Th1 and Th17 frequencies and this effect was abolished when ACM was treated with an adiponectin neutralizing antibody. Collectively, these data reveal a novel role of adiponectin in controlling pro-inflammatory CD4+ T cells during obesity and suggest that the beneficial role of helminth infections and helminth-derived products on obesity and insulin resistance may be in part mediated by adiponectin.